Human immunodeficiency virus type 1 drug resistance in a subset of mothers and their infants receiving antiretroviral treatment in Ouagadougou, Burkina Faso - Serge Theophile Soubeiga; Bapio Valéry Jean Telesphore Elvira Bazie; Tegwindé Rebeca Compaore; Abdoul Karim Ouattara; Théodora Mahoukèdè Zohoncon; Dorcas Obiri-Yeboah; Albert Théophane Yonli; Arsène Zongo; Lassina Traore; Virginio Pietra; Simon Akpona; Serge Diagbouga; et al. (AOSIS, 2018)
The emergence of HIV-1 drug resistance (HIVDR) is a public health problem that affects women and children. Local data of HIVDR is critical to improving their care and treatment. So, we investigated HIVDR in mothers and infants receiving antiretroviral therapy (ART) at Saint Camille Hospital of Ouagadougou, Burkina Faso. This study included 50 mothers and 50 infants on ART. CD4 and HIV-1 viral load were determined using FACSCount and Abbott m2000rt respectively. HIVDR was determined in patients with virologic failure using ViroSeq HIV-1 Genotyping System kit on the 3130 Genetic Analyzer. The median age was 37.28 years in mothers and 1.58 year in infants. Sequencing of samples showed subtypes CRF02_AG (55.56%), CRF06_cpx (33.33%) and G (11.11%). M184V was the most frequent and was associated with highlevel resistance to 3TC, FTC, and ABC. Other mutations such as T215F/Y, D67N/E, K70R, and K219Q were associated with intermediate resistance to TDF, AZT, and 3TC. No mutation to LPV/r was detected among mothers and infants. The findings of HIVDR in some mothers and infants suggested the change of treatment for these persons.